Electrophysiological and radioisotope analysis of ion fluxes induced by salt and oxidative stress in higher plant root cells - Samokhina, Veranika V.; Hryvusevich, Palina V.; Sokolik, Anatoliy I.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2022)
Environmental stresses induce the release of electrolytes from root cells into the extracellular space, including key inorganic and organic ions. This phenomenon is described for salinity, drought, attack of pathogens, exposure to heavy metals, oxidative stress, etc. The efflux of electrolytes is also observed during some processes of normal physiology, being part of the gravitropic response, the formation of polarity and the growth of the cell elongation. Despite the long study of this phenomenon, today its molecular mechanism remains unclear. In the present study, a combined approach based on the labeled atom method (loading isotope 86Rb+ followed by recording the parameters of its efflux from root cells), reverse genetics and the patch-clamp technique has been developed for testing the biophysical and molecular nature of the efflux of electrolytes from the root cells. It has been demonstrated that in the roots of Arabidоpsis thaliana (L.) Heynh., the K+ efflux during salinisation and oxidative stress is catalysed by K+ channels encoded by the GORK gene (guard cell outward-rectifying K+ channel), and the efflux of organic anions – by anion channels encoded by the ALMT1 gene (aluminum-activated malate transporter 1). The characteristics of the combined functioning of these systems under stress have been established.
Keywords: patch-clamp; plant electrophysiology; radioisotope analysis; 86Rb; ion channel; GORK; ALMT1